2001
DOI: 10.1042/0264-6021:3590099
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila haemocyte-specific protein, hemolectin, similar to human von Willebrand factor

Abstract: We identified a novel Drosophila protein of approximately 400 kDa, hemolectin (d-Hml), secreted from haemocyte-derived Kc167 cells. Its 11.7 kbp cDNA contains an open reading frame of 3843 amino acid residues, with conserved domains in von Willebrand factor (VWF), coagulation factor V/VIII and complement factors. The d-hml gene is located on the third chromosome (position 70C1-5) and consists of 26 exons. The major part of d-Hml consists of well-known motifs with the organization: CP1-EG1-CP2-EG2-CP3-VD1-VD2-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 54 publications
1
76
0
Order By: Relevance
“…23) with UAS-GFP and used it to label all postmitotic neurons for cell sorting. The HML-GFP line was originally generated by A. Goto 14 (Nagoya University, Japan) and is available through the Bloomington Stock Center. We used markers specific to different R cell subtypes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23) with UAS-GFP and used it to label all postmitotic neurons for cell sorting. The HML-GFP line was originally generated by A. Goto 14 (Nagoya University, Japan) and is available through the Bloomington Stock Center. We used markers specific to different R cell subtypes.…”
Section: Methodsmentioning
confidence: 99%
“…12) and Kc 9,13 ) have a profile of Dscam isoforms similar to that of S2 cells (data not shown). We isolated hemocytes by FACS from third instar larvae that express GFP under the control of the promoter region of the hemocyte marker hemolectin (hml) 14 . Consistent with a potential hemocyte origin of these cell lines, the spectrum of Dscam isoforms of primary hemocytes was overall similar to and had the same restriction of exon 9 use as the cell lines.…”
Section: Dscam Expression In Fruit Fly Cell Linesmentioning
confidence: 99%
“…Maturing hemocytes are restricted to the cortical zone of primary lymph gland lobes Mature hemocytes have been shown to express several markers, including collagens (Asha et al, 2003;Fessler et al, 1994;Yasothornsrikul et al, 1997), Hemolectin (Goto et al, 2003;Goto et al, 2001), Lozenge (Lebestky et al, 2000), Peroxidasin and P1 antigen (Asha et al, 2003;Vilmos et al, 2004). We found that the expression of the reporter Collagen-gal4 (Cg-gal4) (Asha et al, 2003), which is expressed by both plasmatocytes and crystal cells, is restricted to the periphery of the primary lymph gland lobe ( Fig.…”
Section: Gross Structure Of the Larval Lymph Glandmentioning
confidence: 99%
“…Additionally, lamellocytes express an uncharacterized surface marker called L1 antigen (Asha et al, 2003). All Drosophila hemocytes specifically express the marker Hemese (He) (Kurucz et al, 2003), while a majority of plasmatocytes and crystal cells express the Collagens Viking and Cg25C (Le Parco et al, 1986;Yasothornsrikul et al, 1997) and the Von Willebrand-like factor Hemolectin (Hml) (Goto et al, 2003;Goto et al, 2001;Sinenko and Mathey-Prevot, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, undifferentiated prohemocyte progenitors and three differentiated blood cell lineages are being distinguished (Rizki, 1978;Shrestha and Gateff, 1982;Lanot et al, 2001;Hartenstein, 2006). Macrophages, or plasmatocytes, that express Peroxidasin (Pxn) (Nelson et al, 1994;Tepass et al, 1994;Stramer et al, 2005) and Hemolectin (Hml) (Goto et al, 2001;Sinenko and Mathey-Prevot, 2004), correspond to vertebrate myeloid cells and represent 90-95% of hemocytes at most developmental stages (Tepass et al, 1994;Lanot et al, 2001;. Crystal cells and lamellocytes are invertebrate-specific, minor cell types limited to specific developmental stages and immune challenges (Lanot et al, 2001;Crozatier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%